Break dormancy, germination and vigor of Brachiaria bri-zantha cv. BRS Piatã - ROMANI, Fernanda; CARVALHO, Ruy Inacio Neiva de (Revista Eletrônica Científica da UERGS, 2016)
This study aimed to identify the best method of breaking dormancy of Brachiaria Brizantha cv BRS Piatã. The treatments were time with sulfuric acid (0, 5, 10 and 15 min) and with and without light during germination. After scraping the seeds were rinsed in deionized water and the germination test was performed on germination paper. The test evaluations were performed three times a week until 21 days. The moisture, thousand seed mass and test weight were determined. The vigor was evaluated by the accelerated aging test. The following variables were calculated: percentage of germination, germination speed index, mean germination time, average speed of germination and entropy. The experimental design was completely randomized in a 4 x 2 factorial design, with one factor represented by the times of acid scarification and another by the presence or absence of light, totaling eight treatments with four replications. The treatment with significant differences by the F test in the analysis of variance were compared by Tukey test (p ≤ 0,05). The vigor of non-germinated seeds was evaluated by the tetrazolium test and of the 320 seeds evaluated, 28% were viable and vigorous, 18% were viable and not vigorous and 54% were not viable. The humidity of the collected seeds was 12,64 %, the weight of a thousand seeds was 4,7 g and the test weight was 87,3 kg hL-1. It was concluded that the best method to break seed dormancy was with scarification with concentrated H2SO4 for 10 minutes without light. In this conditions the best germination percentage of 61,5% was obtained.